Ferroptosis, a Regulated Neuronal Cell Death Type After Intracerebral Hemorrhage - Bai, Qinqin; Liu, Jiachen; Wang, Gaiqing (Frontiers in Cellular Neuroscience, 2020)
Ferroptosis is a term that describes one form of regulated non-apoptotic cell death. It’s triggered by iron-dependent accumulation of lipid peroxides. Emerging evidence suggests a link between ferroptosis and the pathophysiological processes of neurological disorders, including stroke, degenerative diseases, neurotrauma, and cancer. Hemorrhagic stroke, also known as intracerebral hemorrhage (ICH), belongs to a devastating illness for its high level in morbidity and mortality. Currently, there are few established treatments and limited knowledge about the mechanisms of post-ICH neuronal death. The secondary brain damage after ICH is mainly attributed to oxidative stress and hemoglobin (Hb) lysate, including iron, which leads to irreversible damage to neurons. Therefore, ferroptosis is becoming a common trend in research of neuronal death after ICH. Accumulative data suggest the inhibition of ferroptosis may effectively prevent neuronal ferroptosis, thereby reducing secondary brain damage after ICH in animal models. Ferroptosis has a close relationship with oxidative damage and iron metabolism. In this review lies in revealing the pathological pathways and regulation mechanism of ferroptosis following ICH, then offer the potential intervention strategies to mitigate neuron death and dysfunction after ICH.